Inovasi Pendidikan - Muaidi Muaidi (Al-Riwayah : Jurnal Kependidikan, 2016)
Education is a fundamental right of every citizen. However, in practice, not all citizens acquire these rights adequately. One of the reasons of not obtaining such rights is limited ability of the State to provide educational facilities for all citizens, although in fact, the community also has a lot to participate in the provision of educational facilities. So that the rights of citizens can be met, as well as increasing the intelligence of the nation, the government continually improves its ability to provide learning opportunities for all citizens. One of these policies is through a policy of open schools as part of a system of open and distance education. This paper highlights the organizing Junior Open with all its advantages and disadvantages as part of innovation in education